Gagasan Kebijakan Dukungan Pembangunan Pariwisata Bahari Di Pulau Pari, Kepulauan Seribu, DKI Jakarta - Ahmad Prawira Dhahiyat; Fanny Kristiadhi; Nur Sakinah Junirahma; Shafira Bilqis Annida (Yayasan Literasi Sains Indonesia, 2025)
Pari Island has stunning marine tourism potential, but an optimal policy is needed to support the development of tourism on Pari Island. The purpose of this study is to determine the implementation of tourism policies on Pari Island so that it can provide recommendations for future policy improvements in order to achieve the development of marine tourism development. The method used in this research is qualitative with a descriptive approach by conducting interviews with a number of tourists, and local people of Pari Island. The data obtained in this study are primary data through surveys and semi-structured interviews with tourists, tourism managers and local communities to tourists, tourism managers and local communities and secondary data obtained from previous research, as well as literature studies. The results of this study indicate that there is a need for synergy between the government, local communities, and the private sector in designing effective and sustainable policies by looking at the management of tourist destinations by the government, stakeholders, and the community, increasing tourism promotion marketing, welfare of the Pari Island community, law enforcement and supervision.